Social Studies Learning Approaches for Children with Autism Spectrum Disorder at State Tsanawiyah Middle School 3 in Pesisir Selatan - Suryadi Fajri*; Anisyah Anisyah; Nisa Ulaini; Nursyamsi Nursyamsi (Riwayat: Educational Journal of History and Humanities, 2024)
The research is motivated by the presence of students with autism in grades VIII and IX at State Tsanawiyah Middle School 3 in Pesisir Selatan, where they are placed alongside regular students during the learning process. This study aims to understand the efforts of social studies teachers in educating autistic students through learning approaches. It employs a qualitative research design with a case study method. Data collection techniques include observation, interviews, and document analysis. The research findings indicate: 1) Social studies teachers use humanistic and behavioral approaches in the classroom. 2) The steps of the social studies learning approach start with preliminary, core, and closing activities, tailored to the conditions of autistic students. 3) Learning difficulties faced by autistic students include communication issues, social interaction difficulties, sensory disorders, cognitive challenges, and emotional regulation problems. 4) The study finds that only the behavioral approach in grade IX is effective. The ineffectiveness of the humanistic approach for autistic students in grade VIII is attributed to the need for guidance from special education teachers and the lack of training for social studies teachers in teaching students with special needs. 5) The humanistic approach fosters a sense of being loved, which leads to excessive freedom for autistic students, while the behavioral approach in grade IX generates high enthusiasm. However, the learning outcomes remain far from the educational goals